2021
DOI: 10.4236/ajcc.2021.103012
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Current and Future Spatial Distribution Area of Shea Tree (<i>Vittelaria paradoxa</i> C. F. Gaertn) in the Context of Climate Change in Benin

Abstract: In Benin, Shea tree (Vitellaria paradoxa) is one of the agroforestry species of great socio-economic importance for local populations. Given the actual variation in the climate parameters, it is necessary to anticipate the future spatial distribution of Shea trees as an adaptation strategy and for designing relevant conservation strategies. The aim of the present research was to evaluate the influence of climate change on the distribution areas of Shea trees in Benin. Occurrence data consisting of geographic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…These results confirm that B. aegyptiaca is a characteristic species of dry areas of tropical Africa and tolerates low precipitation (<1000 mm) but high temperature (≈ 40 C). This corroborates the previous findings that mentioned moisture index arid of the quarter (Mwakapeje et al, 2019) and rainfall driest month (Avaligbé et al, 2021;Hounkpèvi et al, 2016) as the most important ecological factors for some plants distribution. In addition, the soil parameter introduced in the model had a positive impact on the prediction of the habitats for B. aegyptiaca.…”
Section: Discussionsupporting
confidence: 93%
“…These results confirm that B. aegyptiaca is a characteristic species of dry areas of tropical Africa and tolerates low precipitation (<1000 mm) but high temperature (≈ 40 C). This corroborates the previous findings that mentioned moisture index arid of the quarter (Mwakapeje et al, 2019) and rainfall driest month (Avaligbé et al, 2021;Hounkpèvi et al, 2016) as the most important ecological factors for some plants distribution. In addition, the soil parameter introduced in the model had a positive impact on the prediction of the habitats for B. aegyptiaca.…”
Section: Discussionsupporting
confidence: 93%
“…In the context of climate change, a modelling study has concluded that habitat protection and restoration could be achieved in Benin by the domestication of the species to both conserve V. paradoxa and support farmers' livelihoods [126].…”
Section: Commercialization Of Productsmentioning
confidence: 99%